2016
DOI: 10.5812/asjsm.35018
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Characteristics of Performance-Enhancing Drug Use Among Bodybuilding Athletes in the South of Iran, Bushehr

Abstract: BackgroundSeveral reports have implied progressive increase of performance-enhancing drug (PED) use among Iranian athletes. More importantly, most of the previous research in the Iranian population had mainly focused on the anabolic steroid abuse, and ignored other agents.ObjectivesThe aim of this study was to investigate the prevalence and characteristics of PED use among bodybuilding athletes in Bushehr, south of Iran.MethodsFour hundred and fifty three male bodybuilding athletes were recruited from Bushehr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 21 publications
3
26
0
7
Order By: Relevance
“…We included published empirical records on AAS from searches in the twenty-one countries located in the Eastern Mediterranean region. The types of records included were survey studies in Saudi Arabia (Al Bishi and Afify 2017; Al Al Nozha and Elshatarat 2017;Alharbi et al 2019;Althobiti et al 2018;Bahri et al 2017;Jabari et al 2016), United Arab Emirates , Kuwait Alsaeed and Alabkal 2015;Khullar et al 2016), Iran (Allahverdipour et al 2012;Angoorani and Halabchi 2015;Asr et al 2018;Bordbar et al 2014;Fijan et al 2018;Haerinejad et al 2016;Jalilian et al 2011;Kargarfard et al 2015;Mohammad 2014;Nakhaee et al 2013;Razavi et al 2014;Rezaei 2017;Saeidinejat et al 2017;Sepehri et al 2009;Sobhanian et al 2013), Iraq Habeeb et al 2012), Lebanon Melki et al 2015), Jordan Wazaify et al 2014), Pakistan Uddin et al 2019;Zafar et al 2018), and Sudan (Khidir and Mahmoud 2018); and conference proceedings from Bahrain ) (see Table 2). Correlational study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included published empirical records on AAS from searches in the twenty-one countries located in the Eastern Mediterranean region. The types of records included were survey studies in Saudi Arabia (Al Bishi and Afify 2017; Al Al Nozha and Elshatarat 2017;Alharbi et al 2019;Althobiti et al 2018;Bahri et al 2017;Jabari et al 2016), United Arab Emirates , Kuwait Alsaeed and Alabkal 2015;Khullar et al 2016), Iran (Allahverdipour et al 2012;Angoorani and Halabchi 2015;Asr et al 2018;Bordbar et al 2014;Fijan et al 2018;Haerinejad et al 2016;Jalilian et al 2011;Kargarfard et al 2015;Mohammad 2014;Nakhaee et al 2013;Razavi et al 2014;Rezaei 2017;Saeidinejat et al 2017;Sepehri et al 2009;Sobhanian et al 2013), Iraq Habeeb et al 2012), Lebanon Melki et al 2015), Jordan Wazaify et al 2014), Pakistan Uddin et al 2019;Zafar et al 2018), and Sudan (Khidir and Mahmoud 2018); and conference proceedings from Bahrain ) (see Table 2). Correlational study.…”
Section: Resultsmentioning
confidence: 99%
“…The adverse effects of AAS use were not investigated by all studies, with twenty-four papers not reporting on these effects. Self-reported effects by the remaining studies in Kuwait, Bahrain, Saudi Arabia, Iran, and Jordan were aggression, depression, sexual problems, increased appetite, acne, hair loss, gynecomastia, mood changes, fluid retention, headaches, increased hair growth, cardiovascular problems, psychiatric issues, and hepatic and renal damage Alsamani et al 2017;Althobiti et al 2018;Bahri et al 2017;Haerinejad et al 2016;Hussain et al 2018;Razavi et al 2014;Tahtamouni et al 2008;Uddin et al 2019;Wazaify et al 2014). The study by Habeeb et al (2012) stated that most AAS users reported the use of only dietary supplements initially, but on recommendation of others, initiated the use of AAS to improve performance.…”
Section: Aas Regimes Of Use In the Eastern Mediterranean Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most stimulants have caffeine and are used almost daily due to severe requirements during training, and the long-term effects of these substances are yet not completely known (14). Previous studies show that a great part of AAS users combine different steroids, usually in higher doses than normally recommended and for a longer time (2,15), which makes research in this field important to better know the effects of this practice. The most used substances are nandrolone and testosterone, probably due to their low cost (16).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…The use of anabolic-androgenic steroids (AAS) among physical activity practitioners has increased in the last years, and it is associated with body image disorders and clinical complications, including kidney disease (1)(2)(3). In Brazil, the estimated prevalence of AAS use among recreational physical activity practitioners varies from 2.1% to 31.6% (4).…”
Section: Introductionmentioning
confidence: 99%